Gamification of Wordwall Maze Chase as a STEM-Based Learning Media to Improve Students' Creative Thinking Skills (UM Purwokerto Press, 2023)
This study aims to determine the influence of Wordwall Maze Chase gamification as a STEM-based digital learning medium on improving students' creative thinking skills. This research uses a quantitative type of research. The study subjects were grade 5 elementary school students; as many as 31 respondents were selected with purposive sampling techniques. The data collection instrument uses an online questionnaire via a google forms link. The Pearson's correlation test showed that STEM-based Wordwall Maze Chase gamification learning media affected students' creative thinking skills by 0.926, which means it has a perfect correlation. Based on research in the field, using Wordwall Maze Chase gamification media has problems with cellphone performance and student screen resolution; the smaller the screen, the smaller the display of images and writing is also tiny. Learning using STEM-based Wordwall Maze Chase gamification media can be implemented in science, language, social science, and mathematics learning materials.